Central American Thought in the 19th Century: Politics and Education - Camacho Guzmán, Gustavo (2017)
The nineteenth century marked the political and social action of the Central American region. Through the essay, the intellectual thought of the outstanding figures of this isthmus became prolific. Their reflections were oriented towards the creation of proposals on new ways of life in the old colonies. At the same time projects for the national identity of the independent countries of the region also appeared. This article provides a brief overview of the main positions in education and religion cutting across the political and cultural praxis of these intellectuals.